CONSTRUCTION WATER SUITABILITY MAPS OF TIGRIS RIVER FOR IRRIGATION AND DRINKING USE (Journal of Engineering, 2024)
The Tigris River is one of two major sources of surface water in Iraq, with 1900 km length, 1415 km of which are in Iraq. Increasing demands of the river water for beneficial uses lead to increase the concern about its quality.World Health Organization (WHO, 2004) and Iraqi Quality Standards (IQS, 2001) have been adopted along the river to compare and examine the degree of permissibility of polluted parameters T.H, SO4, CI¹, and T.D.S for drinking use, whereas American Salt Laboratory Standards has been adopted basing on SAR and EC for irrigation use. Different international methods have been applied to classify the water quality index for the Tigris River at north of Baghdad station which are Brown (1970), Mecllelend (1974), and Bhargava (1983).A general program was constructed to estimate the surface water quality variation with time and location for drinking and irrigation adopting Bahrgava, 1983 method, since it is more effective in dealing with many sensitive functions related to the pollutant parameters through the analysis of TH, SO, CI, T.D.S, EC, Ca SAR, pH, and BOD which are the relative parameters to the previous mentioned beneficial uses.The program use Visual Basic Studio, 2008 language as a tool because it is easy to operate automatically by engineers or the decision makers for the water quality assessment. Thirteen stations along Tigris River were taken in the analysis, starting at Feeshkabour and ending at Al-Qurna. The historical recorded data which were used had been selected through 2007/2008 as a monthly base In general, the results showed that the Tigris River is class 1 to Il for irrigation use, while its class ranges from II-V for drinking use. According ing to these classes, the Tigirs River is divided into two reaches as follows:From Feeshkhabour to Tarmiyah, the water quality index (WOI) is classified as class 1 for irrigation, and class 11 for drinking use as class for From North of f Baghdad till Qurna, WQl is classified Il for irrigation, and class IV drinking use. The results also indicate that there is an increase in Till values leading to deterioration in water quality for drinking use, also, an increase in SOU parameter after Tarmyah, and C parameter after Kut that affects the suitability of water for irrigation use.Finally, different suitability maps are constructed to classify water of 2007/2008 for irrigation and drinking use, which will be a base to trace the type of pollutants and their weight that cause the deterioration of the previously mentioned uses.Finally, different suitability maps are constructed to classify water of 2007/2008 for irrigation and drinking use, which will be a base to trace the type of pollutants and their weight that cause the deterioration of the previously mentioned uses.Finally, different suitability maps are constructed to classify water of 2007/2008 for irrigation and drinking use, which will be a base to trace the type of pollutants and their weight that cause the deterioration of the previously mentioned uses.